Estimation of active drag using an assisted tow of higher than max swim velocity that allows fluctuating velocity & varying tow force - Mason, B.; Sacilotto, G.; Menzies, T. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to identify if an improved active drag profile could be obtained when estimating active drag using the A.I.S. method of assisted towing, if the tow velocity permitted intra stroke velocity fluctuations that were initiated by the propulsive actions of the swimmer, as opposed to using a tow of constant velocity. When the tow velocity did allow such fluctuations the active drag profile of the swimmer appeared to be less complicated and more accurately representative of the swimmer's actual active drag profile than when a tow of constant velocity was used. There appeared to be very little difference in the active drag profile of the swimmer with a tow that incorporated the intra stroke velocity fluctuations, whether the mean velocities were used in the computation or whether the velocity parameters at the various intervals were used.